Semantic networks of keywords from Brazilian dissertations on physics teaching - Nascimento, J. O. do; Monteiro, R. L. S.; Moreira, D. M.; Gonçalves, M. A. M. Simões; Pereira, H. B. de Barros (Discontinuity, Nonlinearity, and Complexity, 2026)
Metrics of social and complex networks can be used in the study of emergent patterns in semantic networks. The goal of this article is to analyze the semantic network formed by the keywords of theses and dissertations on physics teaching that were defended in Brazil between the years 1996 and 2006. We describe the method used for constructing the network, including the keywords. We analyze the network’s properties in local and global contexts. We study which keywords are presented as cut points, since their removal from the network result in a number of components greater than one. Our results suggest that the network is small–world and scale–free. In addition, using the proposed method, we verified thatmost of the topics emphasized in the network are related to the education of physics instructors and not to methods of teaching physics at different levels.